Liver Regeneration After Major Liver Resection for Hepatocellular Carcinoma in the Elderly. Issue 4 (20th April 2020) - Yasuda, Satoshi; Nomi, Takeo; Hokuto, Daisuke; Yoshikawa, Takahiro; Matsuo, Yasuko; Sho, Masayuki
Abstract: Background : With an aging population, more elderly patients are being considered for hepatic resection for hepatocellular carcinoma (HCC). This study aimed to evaluate postoperative outcomes including liver regeneration after major hepatectomy for HCC in the elderly. Methods : We assessed 41 patients who underwent major hepatectomy (≥3 segments) at our institute between 2000 and 2013. Patients were divided into two age groups, elderly group (age ≥70 years, n = 23) and younger group (age <70 years, n = 18). Clinicopathological data and outcomes were retrospectively compared. To evaluate the effect of aging on liver regeneration, we measured liver volumes preoperatively and at 1 and 6 months after liver resection using a 3D simulation imaging system. Results : Overall and major complications after hepatectomy were not different between elderly and younger groups, and no case of mortality was recorded. Moreover, recurrence-free and overall survivals were similar in both groups. With regard to liver regeneration, no differences were observed between elderly and younger groups at 1 and 6 months after liver resection. Baseline liver functions were comparable between the groups. Furthermore, the only factor associated with liver regeneration was resected liver volume ( R 2 = 0.631, p < 0.001). Age was not correlated with liver regeneration rate ( R 2 = 0.00537, p = 0.695). Conclusions : Liver regeneration after major hepatectomy for HCC was not affected by age and that resected liver volume is an important factor for liver regeneration. Short- and long-term outcomes after major hepatectomy were similar in elderly and younger patients.